144 THE EFFECTIVENESS OF AN HIV/SEXUALLY TRANSMITTED DISEASE RISK INTERVENTION ON INCARCERATED ADOLESCENTS' SEXUAL KNOWLEDGE, SKILLS, AND BEHAVIOR INTENTIONS. (1st January 2006) - Dahl, A. L.; Smith, T. B.; Elliott, P.; Sturdevant, M. S.
Abstract : Purpose of Study: Our goal was to report preliminary findings regarding the effect of an HIV/sexually transmitted disease (STD) educational intervention on the HIV knowledge, skills, and behavioral intentions of incarcerated adolescents. Compared to their school-based peers, incarcerated adolescents report higher rates of many behaviors correlated with HIV transmission. The self-contained environment of juvenile detention centers provides an opportunity to implement interventions capable of reducing high-risk sexual behaviors. The chosen intervention addressed adolescents who are currently sexually active and accounted for the fact that knowledge and risk perception have little effect on adolescent behavior. Additionally, it presented HIV-risk reduction skills, such as communication between sexual partners and accurate perceptions of peer norms, which have shown to strongly impact sexual decision-making in prior studies. Methods Used: Adolescents completed a self-report survey prior to and immediately following an 8-hour HIV/STD educational intervention conducted in two youth detention centers. The pre- and post-intervention group means for each survey item or multi-item scale were compared. Summary of Results: Among 53 participants, the mean age was 15.58, and 30% were male. African Americans comprised 60% and whites 34%. Pre-intervention, 83% reported having had sexual intercourse. Significant increases were found in HIV/STD knowledge (14.7%, p < .01), condom acquisition skills (9.75%, p < .05), impulse control skills (10.0%, p < .1), and the belief that sex during adolescence impedes future goals (9.25%, p < .1). Conclusions Reached: Preliminary findings suggest that the chosen intervention significantly improved crucial factors in sexual decision-making while other sexual beliefs proved more resistant to change. However, even modest changes in sexual behavior intentions and skills may lead to reductions in HIV/STD transmission among high-risk, sexually active adolescents.